Der Zusammenhang des dynamischen Kraftmaximums in der Kniebeuge mit Sprintleistungen zwischen 5 und 30 Metern - Möck, S.; Hartmann, R.; Wirth, K.; Mickel, C. (Leipziger Sportwissenschaftliche Beiträge, 2016)
Short-distance sprints up to 30 Meters display a skill relevant for ones performance in team sports. Research covering the relationship between shortdistance sprint performance and the one-repetition-maximum in the squat fail to deliver consistent results while examining predominantly single intercepts. The present study compares the relationships with several intercepts up to 30 Meters. The results demonstrate that the dynamic maximum force of the lower extremities` extensors display a fundamental supposition for short-distance sprinting and thus should be incorporated into training.